Análise diplomática digital sobre o certificado nacional de vacinação da COVID-19 - COSTA, Yago de Oliveira (2024)
Since the XVII century, Diplomatics intent was to establish the authenticity of documents. With the improvement of information technology and communication, promptness of the form to obtain information, it had a precision to adapt Diplomatics, facing several paradigms, to establish a relation with record from a certain period. Digital documents emerge in response to the necessity that seeks to optimize time and facilitate the use of documentation. The COVID-19 National Vaccination Certificate (NVC), emerged from the necessity of quantifying vaccinated people and testifying to Brazilian people, to vaccinate all population and try to fight the COVID-19 virus. Regarding to the main objective, this study seeks to demonstrate which elements compose the Covid-19 NVC issued by the Connect-SUS App, guaranteeing its authenticity. This study highlights three specific objectives: to identify the document structure; make a diplomatics analysis about the elements/characters distribution that allow the authenticity of Covid-19 NVC; and demonstrate aspects and characterization of Covid-19 NVC. Thus, the methodology used might be categorized as a case study, which will be a descriptive approach and exploratory, with a quantitative and qualitative character. With the help of Digital Diplomatics Analysis, intend to identify its elements/characters that will allow us to attach its authenticity. The research demonstrated that was possible to verify all elements present in Covid-19 NVC that attach its authenticity, and the maintenance of elements of the digital document and its meanings, supporting the use of the “ideal” Diplomatics method, varying according to the use and the chronological paradigms which the document remains. Emphasizing that the characterization was carried in a Conceptual Level in PDF format, once it presents its modeling/structural functions, activities, and elements like the analogical document. On the other hand, the certificate format was exported to XML 1.0, preserving the metadata. in addition, the importance of the use of certificates of the vaccinal cycle of the population was verified